Informal finance in China 2017-2018 - Deakin, Simon F. (UK Data Service, 2019)
This dataset consists of transcripts and notes of interviews conducted in China between April 2017 and December 2018. The interviews were on the theme of informal finance in China and its recent transformation in the light of technological and regulatory changes. The interviewees included executives in financial and technological companies, officials, judges and lawyers. China's rapid economic growth in recent decades has been attributed to its reliance on informal contracting and trust-based relationships. This claim is a reflection of the absence in China of some of the more formal legal and regulatory institutions of the market economies of the global north. Although the claim that China lacks formal legal mechanisms of market governance may have been somewhat overstated, it is the case that informal finance, particularly in the form of trade credit, family lending and communal investing, has played a major role in supporting China's growth. The prevalence of informal finance constitutes a significance source of flexibility for China's economy given the limitations of the formal sector, which remains dominated by state-owned banks lending largely to state-owned enterprises. Informal finance is also evolving quickly and is converging with the use of internet technologies to deliver finance ('fintech') through such mechanisms as crowdfunding. However, there are downsides to the reliance of the Chinese economy on informal finance and significant risks arise from its convergence with fintech. The large shadow banking sector, by virtue of its positioning outside most of the regulations applying to mainstream banks, adds to systemic risks. The formal and informal sector coexist in an uneasy relationship: they may substitute for each other, or provide complementary modes of finance, but they can also operate to reinforce and magnify systemic risks, as in the case of the crisis in Wenzhou after 2011. Similarly, the rise of fintech is a double edged sword. On the one hand, cloud computing and big data may be facilitating new forms of social credit and collective investment schemes which have the potential to meet the needs of the growing social credit sector. Crowdfunding may provide a new and flexible form of financing for start-ups and innovative ventures. However, these new forms of finance also have the potential to undercut or render otiose regulations designed to maintain market transparency, and to intensify the risks facing investors. Against this background, the project explores the phenomenon of informal finance in China, identifies the risks and potential associated with it, and assesses how regulation can best respond to the risks while not sacrificing the innovations and flexibility associated with it, particularly in the context of 'fintech'.